2016
DOI: 10.7717/peerj.1711
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asymptomatic urinary tract infections in morbidly obese dogs

Abstract: Background. Obesity has reached epidemic proportions in dogs and, as in humans, cost of care has increased due to associated comorbidities. In humans, asymptomatic urinary tract infections (UTI) may be more prevalent in the obese. Asymptomatic bacteriuria (AB) is the term used when UTI are asymptomatic. We hypothesized that morbidly obese dogs are similarly more likely to have asymptomatic bacteriuria than lean, overweight, and moderately obese dogs.Methods. A retrospective study was undertaken to explore a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
3
24
1
1
Order By: Relevance
“…24 The prevalence of subclinical bacteriuria has been reported in healthy female dogs (8.9%), dogs presenting for elective surgical procedures (8.9%) and morbidly obese dogs (25%). [25][26][27] These data support the necessity of quantitative urine cultures as an indicator of bacteriuria in dogs without urinary tract signs. Subclinical bacteriuria has been reported in dogs with inflammatory skin disease treated chronically with ciclosporin in which nine of 71 (13%) dogs had positive urine cultures at a single time point of sample collection.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…24 The prevalence of subclinical bacteriuria has been reported in healthy female dogs (8.9%), dogs presenting for elective surgical procedures (8.9%) and morbidly obese dogs (25%). [25][26][27] These data support the necessity of quantitative urine cultures as an indicator of bacteriuria in dogs without urinary tract signs. Subclinical bacteriuria has been reported in dogs with inflammatory skin disease treated chronically with ciclosporin in which nine of 71 (13%) dogs had positive urine cultures at a single time point of sample collection.…”
Section: Discussionsupporting
confidence: 57%
“…Urinary tract infection has been shown to occur in 17% of dogs presenting for necropsy for various reasons not necessarily related to urinary tract disease . The prevalence of subclinical bacteriuria has been reported in healthy female dogs (8.9%), dogs presenting for elective surgical procedures (8.9%) and morbidly obese dogs (25%) . These data support the necessity of quantitative urine cultures as an indicator of bacteriuria in dogs without urinary tract signs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the findings from a previous study do not support the treatment of subclinical bacteriuria in healthy female dogs . However, the true risk for subclinical bacteriuria leading to a UTI, ascending infections, and pyelonephritis remains to be investigated, and other studies question the indication for antibiotic treatment in certain patients at risk for UTI (ie, morbidly obese dogs) . The need for treatment in cases with subclinical bacteriuria associated with concurrent immunosuppressive treatment, hyperadrenocorticism, diabetes mellitus, and CKD is more debatable and would be influenced by the colony count, bacterial species identified, past history of the patient including presence of other concurrent diseases, and clinician judgment.…”
Section: Discussionmentioning
confidence: 97%
“…41 However, the true risk for subclinical bacteriuria leading to a UTI, ascending infections, and pyelonephritis remains to be investigated, and other studies question the indication for antibiotic treatment in certain patients at risk for UTI (ie, morbidly obese dogs). 42 The need for treatment in cases with subclinical bacteriuria associated with concurrent immunosuppressive treatment, hyperadrenocorticism, diabetes mellitus, and CKD 43 is more debatable and would be influenced by the colony count, bacterial species identified, past history of the patient including presence of other concurrent diseases, and clinician judgment. In this study, we found a very low prevalence of pyelonephritis at necropsy (0.4-1.3%), and an even lower prevalence of asymptomatic pyelonephritis (38% of dogs did not show classic clinical signs of pyelonephritis).…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo retrospectivo recente descreveu que cães obesos (com > 45% de gordura corporal) podem apresentar infecção no trato urinário, sugerindo uma relação entre a obesidade e a predisposição para este tipo de infecção (Wynn et al, 2016). As alterações encontradas na urinálise, que possibilitaram o diagnóstico de cistite bacteriana em algumas cadelas do grupo obesidade, concordam com os resultados deste estudo.…”
Section: Correlaçõesunclassified